M2-like macrophage-derived exosomes inhibit osteoclastogenesis via releasing miR-1227-5p - Shan Chen; Jian Liu; Lilei Zhu (Immunobiology)
Macrophages play a pivotal role in regulating inflammatory response in periodontitis, a condition characterized by excessive osteoclast differentiation. This study aimed to investigate whether exosomes derived from M2 macrophages regulate osteoclast differentiation and to identify the underlying molecular mechanisms. Exosomes were isolated from M2 macrophages and used to treat osteoclasts. Osteoclastogenesis was assessed using tartrate-resistant acid phosphatase staining and reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The molecular mechanism was evaluated using microarray analysis, RT-qPCR, dual-luciferase reporter analysis, and RNA pull-down assay. The results showed that exosomes from M2 macrophages inhibited receptor activator of nuclear factor κ-B ligand (RANKL)-induced osteoclast differentiation. Additionally, miR-1227-5p expression in osteoclasts was increased after treatment with exosomes, and inhibition of miR-1227-5p counteracted the suppressive effects of exosomes on osteoclastogenesis. Moreover, OSCAR is a target of miR-1227-5p. In conclusion, exosomal miR-1227-5p suppresses osteoclast differentiation, potentially via targeting OSCAR. These findings provide new insights into the pathogenesis of periodontitis.